Neuroendocrine and Metabolic Disorders in Bulimia Nervosa - Milano, Walter; Capasso, Anna (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2018)
Background and Objective: Bulimia nervosa, is an eating disorder characterized by excessive influence of weight and body shape on the levels of self-esteem, with pervasive feelings of failure and inadequacy. The eating is characterized by the presence of episodes of uncontrolled eating (Binge), during which the person ingests mass wide variety of foods and the feeling of not being able to stop eating. This review focuses on the metabolic and hormonal alterations in the in bulimia nervosa. Methods: A literature search was conducted using the electronic database Medline and PubMed and with additional hand searches through the reference list obtained from the articles found. Journal were searched up to 2015. Inclusion criteria were: 1) full text available in English; 2) published in a peerreviewed journal and using the following keywords: neurotransmitters (AgRP, BDNF, αMSH, NP Y, endocannabinoids, adiponectin, CCK, ghrelin, GLP-1, insulin, leptin, PP, PYY), hormones (FSH, LH, estrogen, progesterone, testosterone) and bulimia nervosa, eating disorders. Results: All data reported in the present review indicated that changes in the central and peripheral neuroendocrine equilibria may favor the onset and influence the course and prognosis of a DA. However, it is still questionable whether the alterations of the peptides and hormones regulating the mechanisms of eating behavior are the cause or consequence of a compromised diet. Conclusion: The results of the present review indicate that the altered balance of the various peptides or hormones can be relevant not only for the genesis and / or maintenance of altered dietary behaviors, but also for the development of specific psychopathological aspects in eating disorders.
Keywords: bulimia nervosa